Effect of Foreign Ownership, Audit Committees, Leverage, And Information Asymmetry on Earnings Management with ESG Disclosures as a Moderating Variable - Vinola Herawaty; Faisal Reza Mahendra (Universitas Bangka Belitung, 2026)
This study explores the influence of foreign ownership, audit committee presence, leverage, and information asymmetry on earnings management, with Environmental, Social, and Governance (ESG) disclosure considered as a moderating variable and firm size treated as a control variable. The analysis utilized panel data regression, drawing from a sample of companies listed on the main board of the Indonesia Stock Exchange (IDX) between 2020 and 2023. A purposive sampling method was applied, and outlier cases were excluded, resulting in 115 valid observations. The results indicate that information asymmetry has a significant positive relationship with earnings management. However, this relationship is weakened when moderated by ESG disclosure. In contrast, foreign ownership, audit committee composition, leverage, and standalone ESG disclosure show no significant individual impact on earnings management. Moreover, ESG disclosure does not serve as a mediating factor between foreign ownership, audit committee presence, or leverage and earnings management. These findings highlight the critical role of ESG transparency in curbing earnings management practices that may be detrimental to stakeholder interests.